Solitary median maxillary central incisor: A case report of a rare dental anomaly - Deepak Chandrasekaran; Arif Yezdani; Faizal Tajir; B Saravanan; L Rajasekar (Wolters Kluwer Medknow Publications, 2015)
The solitary median maxillary central incisor (SMMCI) syndrome is a rare dental anomaly and has an incidence of 1:50,000 live births. In SMMCI, there is only one central incisor present, and it develops exactly at the midline. SMMCI occurrence has been described with growth hormone deficiency or other structural anomalies in the midline of the body. In this case, the 8-year-old female patient reported a single median maxillary central incisor with missing maxillary and mandibular frena, with apparently no other abnormalities. Early diagnosis and recognition of SMMCI are important for all practicing Orthodontists, as it may be a sign of other severe congenital or developmental abnormalities.